Rancang Bangun Aplikasi Rekam Medis pada Bagian Rawat Jalan di Rumah Sakit Darus Syifa' Surabaya - Anggara, Faris Widi; Jusak, Jusak; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Medical records is a document were used to document patient's health history. Medical records are very important, because it used as a reference for doctor's examination. But in the process of making and keep of medical records Darus Syifa' Islam Hospital has a few problems. First, medical records is still stored manually. These data is stored at the same filing cabinet. When grab a data, the officer is difficult to find medical records data and sometime the data is missing. So that the officer must make a new medical records. In this condition, it can impact the examination who do by the doctor because they do not know the history of previous examination. Second, the process to make a medical record is still manually. The other job description of medical record officer is make a summary of medical record data. The summary is contain medical record which made every month.The difficulties of the making these summary is when summarize all the data, because not all the data is completely stored. Beacuse the data is missing, it makes the content of data is not complete and duplicated. To solve these problems, Darus Syifa Islam Hospital need a system to help the process of records and storage of data, so these mistakes in the previous process not happen again, and result is corresponding with needs.